2023
DOI: 10.1146/annurev-fluid-120720-014714
|View full text |Cite
|
Sign up to set email alerts
|

Sharp Interface Methods for Simulation and Analysis of Free Surface Flows with Singularities: Breakup and Coalescence

Abstract: A common feature of many free surface flows—drop/bubble breakup or coalescence and film/sheet rupture—is the occurrence of hydrodynamic singularities. Accurately computing such flows with continuum mechanical, multidimensional free surface flow algorithms is a challenging task given these problems’ multiscale nature, which necessitates capturing dynamics occurring over disparate length scales across 5–6 orders of magnitude. In drop breakup, the thinning of fluid threads that form and eventually pinch-off must … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 146 publications
0
12
0
Order By: Relevance
“…8−10 The neck expansion resulting from the quasi-static bubble coalescence has been extensively studied. 3,11,12 In this case, the bubbles approach each other slowly, and no gas is introduced during the merging process. In contrast, the lateral coalescence of two growing bubbles is a common phenomenon near gas distributors in industrial applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8−10 The neck expansion resulting from the quasi-static bubble coalescence has been extensively studied. 3,11,12 In this case, the bubbles approach each other slowly, and no gas is introduced during the merging process. In contrast, the lateral coalescence of two growing bubbles is a common phenomenon near gas distributors in industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Bubble coalescence plays a crucial role in the bubble size and void fraction distribution in gas–liquid two-phase flow systems and thus heat and mass transfer efficiency. , When two bubbles come into contact and merge, a kind of hydrodynamic singularity arises. , Subsequently, an air bridge (often called a “neck”) forms, connecting the two merging bubbles. Finite-approach velocities, arbitrary surface shapes, and fluid properties contribute to the variety. The neck formation and temporal evolution are critical features in the study of bubble coalescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And the capillary‐inertia model and scaling laws have been proposed to describe r n . [ 11–13 ] Paulsen et al [ 14 ] demonstrated that if the Ohnesorge number (Oh=μnormall/ρnormallσRnormalb) is smaller than 0.3, the inertia dominates over the viscous stress after r n reaches 2.8μnormalgRnormalb/ρnormallσ. Here, μ l , ρ l , and σ are the viscosity, density, and surface tension of the liquid, respectively; R b is the bubble radius at contact; and μ g is the gas viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Without gas injection for static bubble coalescence, the neck evolution is solely driven by the unbalanced surface tension. [3,11] Nevertheless, the expansion characteristics of the neck with air injection and the flowrate effects remain unclear. Hereafter, we briefly review some studies on the static coalescence of two bubbles or drops without air or liquid injection.…”
Section: Introductionmentioning
confidence: 99%